Strengthening health systems to address inequities in COVID-19 vaccine access in the Asia-Pacific region - Valerie Gilbert Ulep (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2022)
The economic and health recovery of countries in the Asia-Pacific region from the pandemic is hinged on the rapid and equitable deployment of safe and effective COVID-19 vaccines. However, in the initial years of the COVID-19 vaccine roll-out, highly unequal distribution of vaccines occurred across and within countries. Even though the tight global supply was indeed an issue, health system challenges, particularly in terms of financing, service delivery, human resources, regulatory capacity and governance, played an important role in the inequitable deployment of vaccines. Recommendations given in this paper revolve around the importance of strengthening the health system to enable the equitable allocation and distribution of COVID-19 vaccines.
Keywords: I14; I18; 330; COVID-19; vaccines; health systems; inequities; Asia-Pacific